Variability of Hydrological Parameters and Water Balance Components in Small Catchment in Croatia - Lidija Tadić; Tamara Dadić; Marija Leko-Kos (Advances in Meteorology)
Analysis of small catchment area in Croatian lowland with its hydrological characteristics in the period between 1981 and 2014 was carried out in order to define significance of change in hydrological and meteorological parameters (precipitation, air temperatures, and discharges) and water balance components (deep percolation and potential evapotranspiration). There was no significant land use change in the observed period, so all changes in hydrological processes can be considered to be without human impact in the last 35 years. Application of RAPS (Rescaled Adjusted Partial Sums) on all data series distinguished two subperiods with different length but the same behaviour. The first subperiod was a period characterised by the decrease, starting in 1980 and finishing between 1991 and 1995, while the second one was a period characterised by the increase of parameters in all analyses, starting between 1991 and 1995 and finishing in 2001. In comparison to the analysis of climate change impacts per decade, this approach is much more appropriate and gives insight into variations throughout the entire observed period. The most variable but not significant parameters are precipitation and discharges, especially in the second subperiod which has a major impact on occurrence of hydrological hazards such as droughts and floods and makes great pressure and responsibility on water management system.